Diagnostic accuracy of leukocyte esterase in confirmed cases of urinary tract infection in children - Arif, Anam; Afzal, Muhammad Faheem; Hamid, Haroona (Journal of Rawalpindi Medical College, 2022)
Background: Gold standard for the diagnosis of urinary tract infections (UTIs) is urine culture, but it takes longer for bacterial growth on culture media. Leukocyte esterase is a simple strip testing of urine sample, so it takes less time in diagnosing cases of UTI. Objective: To determine the diagnostic accuracy of leukocyte esterase for detection of urinary tract infection in children taking urine culture as the gold standard. Materials and Methods: This cross-sectional study was conducted in the Department of Pediatrics, —removed for blond review—from April to October 2017. Children of both genders between 2-12 years of age having clinical findings consistent with the operational definition of UTI were included in this study. Clean catch, midstream urine sample was collected in a sterile container for culture and test strip was dipped in urine sample for leukocyte esterase. Results: Total 215 Children were included in the study.The mean age of the children was 7.15±3.36 years. There were 118 (54.9%) males and 97(45.1%) females in this study.37 (17%) were culture positive. Sensitivity, specificity, positive and negative predictive value of leukocyte esterase was 69.77%, 87.79%, 58.82%, and 92.07% respectively. Diagnostic accuracy was 84.19%. Conclusion: Leukocyte esterase is a reliable marker for the screening of urinary tract infection in children 2 years to 12 years of age. Key words: Leukocyte esterase, urinary tract infection, urine culture